2018
DOI: 10.1021/acssuschemeng.8b04105
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Nx Sites Enriched Carbon Micropolyhedrons Derived from Fe-Doped Zeolitic Imidazolate Frameworks with Reinforced Fe-N Coordination for Efficient Oxygen Reduction Reaction

Abstract: Rational design and facile synthesis of highly active and stable electrocatalysts for oxygen reduction reaction (ORR) are crucial in the field of metal-air batteries. Here, we present a facile two-stage thermal synthesis of Fe-N codoped porous carbon (Fe-N/C) with abundant Fe-N x active sites and mesopores from Fe-doped ZIF-8 precursors. The first-stage preheating treatment of the Fe-doped ZIF-8 precursors before the second-stage carbonization is the key to boost the coordination between the doped Fe and N-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Biomass always contains carbon‐based protein and other inorganic salts with low cost and abundant resources, which can be pyrolyzed into porous carbon nanostructures decorated with TM species. For example, animal bones (e.g., cattle bone,36 fish scale,37 peanuts,38 etc.) are one kind of the biomass wastes, which have been widely employed as low‐cost and environment‐friendly precursors to synthesize the hierarchically porous carbon‐based nanostructures.…”
Section: Synthetic Strategies For Porous Carbon Nanostructures Decoramentioning
confidence: 99%
“…Biomass always contains carbon‐based protein and other inorganic salts with low cost and abundant resources, which can be pyrolyzed into porous carbon nanostructures decorated with TM species. For example, animal bones (e.g., cattle bone,36 fish scale,37 peanuts,38 etc.) are one kind of the biomass wastes, which have been widely employed as low‐cost and environment‐friendly precursors to synthesize the hierarchically porous carbon‐based nanostructures.…”
Section: Synthetic Strategies For Porous Carbon Nanostructures Decoramentioning
confidence: 99%
“…We think the formation of Fe 3 N active sites embedded in the carbon matrix of the Fe x NC catalysts was responsible for the high activity and stability. The configuration of Fe‐N could significantly decrease the Mullilken charges of the Fe center, which favored the adsorption of O 2 molecule on the Fe 3 N active sites and thus facilitated the subsequent dissociation of the double bond of O 2 …”
Section: Resultsmentioning
confidence: 99%
“…The configuration of Fe-N could significantly decrease the Mullilken charges of the Fe center, which favored the adsorption of O 2 molecule on the Fe 3 N active sites and thus facilitated the subsequent dissociation of the double bond of O 2 . 74,75 For DMFCs, the penetration of methanol from anode to cathode would increase the overpotential of ORR at the cathode. Therefore, it is crucial for the ORR catalyst to have a high methanol tolerance ability.…”
Section: Resultsmentioning
confidence: 99%
“…who found that a pre‐heating step of the Fe‐ZIF‐8 precursor (200 °C) before carbonisation (800 °C) was key in boosting the coordination between the doped Fe and N‐containing ligands (Figure ). Their optimised catalysts reached ORR catalytic performance with a half‐wave potential of 0.88 V and limiting current density of 6.0 mA cm −2 in 0.1 M KOH …”
Section: Fenx For Electrocatalysismentioning
confidence: 99%
“… Two‐steps synthesis of FeN x @C, electrochemical performance. Reproduced with permission from . Copyright 2018 American Chemical Society.…”
Section: Fenx For Electrocatalysismentioning
confidence: 99%